Blinatumomab versus chemotherapy in first salvage or in later salvage for B-cell precursor acute lymphoblastic leukemia. Issue 9 (29th July 2019) - Dombret, Hervé; Topp, Max S.; Schuh, Andre C.; Wei, Andrew H.; Durrant, Simon; Bacon, Christopher Larry; Tran, Qui; Zimmerman, Zachary; Kantarjian, Hagop
Abstract: Outcomes for adults with relapsed/refractory acute lymphoblastic leukemia (ALL) are poor with chemotherapy, particularly in later salvage. The TOWER study examined survival, remission, bridge to allogeneic hematopoietic stem cell transplantation (HSCT), and safety with blinatumomab versus chemotherapy. This report examined outcomes separately for study treatment as first or later salvage. Adults with Philadelphia chromosome-negative B-cell precursor ALL relapsed/refractory to chemotherapy were randomly assigned 2:1 to receive blinatumomab by continuous infusion for 4 weeks in 6-week cycles, or standard salvage chemotherapy. Overall survival for blinatumomab versus chemotherapy was higher both in first salvage and in later salvage. Safety was similar between patients in first salvage and those in later salvage. Blinatumomab as later salvage was associated with higher complete remission rates and served as a bridge to allogeneic HSCT, supporting the use of blinatumomab in both settings. This study is registered at www.clinicaltrials.gov as #NCT02013167.